Eco-Process Innovation Performance: Production Waste Investigation through Discrete Event Simulation - Suziyana, Mat Dahan; Sha'ri, Mohd Yusof (IOP Publishing, 2019)
Eco-process innovation has been recognised as an effective green strategy for altering manufacturing processes so as to improve a firm’s environmental performance. As many recent eco-innovation studies focusing on perceptual approach of investigating the performance indicators, new study opportunity knocked the door for new knowledge disclosure of operational approach, since it has been largely ignored. This paper aims to assess production waste improvement brought by eco-process innovation implementation in a manufacturing facility. For this purpose, the discrete event simulation approach has been applied to model and simulate the waste rate of previous state and current state of an eco-innovatively improved production line, using the real operational data. Comparison between both states of production system demonstrated a reduction of 0.14% and 0.02% in waste rate at visual mechanical inspection and final test inspection points consecutively, hence confirmed that eco-process innovation practice enabled the improvement of the environmental performance of manufacturing firm. The study is a small part of a larger research work of which the authors are developing indicators for measuring eco-process innovation performance at the firm level.